Advancing social and emotional well-being in Aboriginal and Torres Strait Islander Australians: Clinicians' reflections. (August 2019) - Balaratnasingam, Sivasankaran; Chapman, Murray; Chong, Derek; Hunter, Ernest; Lee, Jason; Little, Carolyn; Mulholland, Kim; Parker, Robert; Watson, Marshall; Janca, Aleksandar
Objective: An expert reference group met on four occasions to consider ways forward in terms of Indigenous mental health. This paper summarises the discussion and recommendations. Conclusion: While the negative effects of colonisation and trans-generational trauma continue, we propose renewed emphasis on improving access, cultural orientation and trauma-informed care, and a focus on the needs of young Indigenous Australians.